Analysis of the Importance Degree and Performance of Internet Service Providers in Makassar City - Haerdiansyah Syahnur; Jafar Basalamah (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2019)
This study aimed to analyze the customer experience seen from the level of actual performance and the level of importance of services provided by internet service providers PT. XYZ in Makassar City. Variables and attributes issued by TM Forum GB 912 consisting of Customer Management, Fulfillment, Assurance, and Billing, are used to analyze the performance provided by customer service in the field. The analysis technique will be carried out using the Importance Performance Analysis and Customer Satisfaction Index consisting of quadrant analysis and gap analysis used to investigate customer satisfaction and identify variables whose performance is deemed to need improvement. Data were collected using a platform-based questionnaire application from 100 respondents selected using random sampling techniques. The results showed that customers were satisfied with the performance and quality of services provided. The customer satisfaction index value obtained by CSI analysis shows a value of 82.006%. In conclusion, that the Fulfillment variable is a service variable that is considered the most important customer and requires improvement because its performance is still relatively low. While the variables considered good and need to be maintained are the Billing variable. Other service variables are sorted based on priority of improvement in a row, namely Fulfillment, Customer Management, and Assurance.